ANALISIS KEBUTUHAN PEMBELAJARAN MATEMATIKA MENGGUNAKAN E-LEARNING BERBASIS PROBLEM BASED LEARNING DI SMP N 2 DENPASAR - Ni Kadek Trisna Prabawati Dewi; I Gusti Ayu Putu Arya Wulandari; I Made Wena (Jurnal Pembelajaran dan Pengembangan Matematika, 2022)
ABSTRACT The purpose of this research is (1) To find out how the needs of teachers and students in learning math using E-learning based on Problem Based Learning in SMP Negeri 2 Denpasar, (2) to find out the factors of obstacle in needs planning efforts of mathematics learning using E-learning based on Problem Based Learning and (3) to find out supporting factors in needs planning efforts of mathematics learning using E-learning based on Problem Based Learning. This research is qualitative research. The subjects in the study mathematics teachers and students in grades IX 1 and IX.2. The instrument used is a questionnaire. The results of this study are (1) 100% of teachers fall into the category of very need and, 39.69% of students are in the category of very need, and 60.31% of students are in the category of need, (2) The obstacle factor experienced by teachers is a less stable network and licensing needs from the leadership. As for learners there are no obstacle factors experienced and (3) There are several supporting factors from teachers and students, namely the availability of devices such as mobile phones, laptops and computers and very adequate internet access. Keyword : Mathematic education; e-learning; Problem based learning ABSTRAK Tujuan penelitian ini adalah (1) Untuk mengetahui bagaimana kebutuhan guru dan peserta didik dalam pembelajaran matematika menggunakan E-learning berbasis Problem Based Learning di SMP Negeri 2 Denpasar, (2) untuk mengetahui faktor kendala dalam upaya perencanaan pemenuhan kebutuhan pembelajaran matematika menggunakan E-learning berbasis Problem Based Learning dan (3) untuk mengetahui faktor pendukung dalam upaya perencanaan kebutuhan pembelajaran matematika menggunakan E-learning berbasis Problem Based Learning. Penelitian ini merupakan penelitian kualitatif. Subjek dalam penelitian ini adalah guru matematika kelas IX dan peserta didik kelas IX 1 dan IX.2. Instrumen yang digunakan berupa kuesioner. Hasil dari penelitian ini adalah (1) 100% guru masuk kategori sangat butuh, 39,69% peserta didik masuk kategori sangat butuh, dan 60,31% peserta didik masuk kategori butuh, (2) Faktor kendala yang dialami guru yaitu jaringan kurang stabil dan diperlukan perizinan dari pimpinan. Sedangkan untuk peserta didik tidak terdapat faktor kendala yang dialami dan (3) Ada beberapa faktor pendukung dari guru dan peserta didik yaitu tersedianya perangkat seperti Handphone, laptop dan komputer serta akses internet yang sangat memadai. Kata Kunci : Pembelajaran Matematika; E-learning; Problem Based Learning